Efek Peningkatan Quality of Work Life dan Motivasi Kerja Terhadap Kinerja Karyawan - Joko, Joko; Tiarapuspa, Tiarapuspa; Ikhwan, HS (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The purpose of this study was to analyze the effect of quality of work life, Work Motivation on Performance. The independent variables in this study are quality of work life, Work Motivation and the dependent variable is Performance. This research was conducted on employees of PPNPN Head Office of the Directorate General of Treasury with a population of 156 people. The measurement of the variables was carried out using a Likert scale. Data analysis was performed using descriptive statistical data analysis methods (average) and structural equation model analysis (SEM). The software used for descriptive data analysis was SPSS and for SEM analysis using AMOS.The results of the study found that there was a positive effect of quality of work life on performance and there was a positive influence of work motivation on performance. The results of this study are the perception of quality of work life and the provision of motivation to improve employee performance